STRATEGY IMPLEMENTATION FACTORS AND PERFORMANCE OF MICROFINANCE INSTITUTIONS IN MACHAKOS COUNTY, KENYA - ALEX MITHIORI KIMANI (Machakos University Press, 2025)
Microfinance institutions play a vital role in financial inclusion, providing access to credit, savings, insurance, and other financial services to low-income individuals and marginalized communities. This study investigated the influence of strategy implementation on the performance of Microfinance institutions (MFIs) in Machakos County, Kenya. Specifically, this study set out to examine the influence of resource allocation, strategy communication, organizational structure and organizational culture on performance of microfinance institutions in Machakos County. The study was guided by the resource-based view theory, managerialism theory, contingency theory and theory of organizational excellence. An explanatory research design was chosen for the study. Closed-ended structured questionnaires were administered by the researcher on the respondents to collect data. The target population was 63 microfinance staff in Machakos County. Thus, the MFIs formed the unit of analysis. The target population for this study comprised the staff in the microfinance branch offices in Machakos County. A pilot test on 6 respondents randomly selected from the target population was conducted to offer preliminary data for the selection of a probability sample and identifying any weaknesses in the research design and instrumentation. The questionnaires were administered physically on drop and pick basis. The collected data was analyzed using SPSS version 26. Multiple regression analysis was carried out to establish the nature and magnitude of the relationship between resource allocation, strategy communication, organizational structure organizational culture and MFIs performance. The findings were presented using tables, graphs and bar charts. The findings showed that effective resource allocation and a strong organizational culture had a positive correlation with firm performance. The study found that resource allocation ((β = 0.382, p value = 0.000), strategy communication (β = 0.247, p value = 0.000) and organizational culture (β = 0.330, p value = 0.000) had a statistically significant positive impact on firm performance. However, organizational structure (β = -0.343, p value = 0.000) had a negative significant effect on performance of MFIs. The study concluded that efficient resource allocation strategies in enhancing firm performance, strategic communication is a critical determinant of firm performance, an overly rigid or bureaucratic organizational structure can impede adaptability and responsiveness to market dynamics and organizational culture is a powerful driver of firm performance within microfinance institutions in Machakos County. The study recommended that policymakers and microfinance institutions (MFIs) should prioritize developing clear guidelines and frameworks for efficient resource allocation, establish structured communication channels that ensure strategic goals are effectively communicated across all levels of the organization and MFIs should consider adopting more flexible organizational structures that align with their operational and strategic needs. The study suggested that future studies should focus on the influence of regulatory changes, economic conditions, and market competition on organizational strategies and performance outcomes.